Altered Viral Fitness and Drug Susceptibility in HIV-1 Carrying Mutations That Confer Resistance to Nonnucleoside Reverse Transcriptase and Integrase Strand Transfer Inhibitors - Hu, Zixin (American Society for Microbiology, 2014)
Nonnucleoside reverse transcriptase (RT) inhibitors (NNRTI) and integrase (IN) strand transfer inhibitors (INSTI) are key components of antiretroviral regimens. To explore potential interactions between NNRTI and INSTI resistance mutations, we investigated the combined effects of these mutations on drug susceptibility and fitness of human immunodeficiency virus type 1 (HIV-1). In the absence of drug, single-mutant viruses were less fit than the wild type; viruses carrying multiple mutations were less fit than single-mutant viruses. These findings were explained in part by the observation that mutant viruses carrying NNRTI plus INSTI resistance mutations had reduced amounts of virion-associated RT and/or IN protein. In the presence of efavirenz (EFV), a virus carrying RT-K103N together with IN-G140S and IN-Q148H (here termed IN-G140S/Q148H) mutations was fitter than a virus with a RT-K103N mutation alone. Similarly, in the presence of EFV, the RT-E138K plus IN-G140S/Q148H mutant virus was fitter than one with the RT-E138K mutation alone. No effect of INSTI resistance mutations on the fitness of RT-Y181C mutant viruses was observed. Conversely, RT-E138K and -Y181C mutations improved the fitness of the IN-G140S/Q148H mutant virus in the presence of raltegravir (RAL); the RT-K103N mutation had no effect. The NNRTI resistance mutations had no effect on RAL susceptibility. Likewise, the IN-G140S/Q148H mutations had no effect on EFV or RPV susceptibility. However, both the RT-K103N plus IN-G140S/Q148H and the RT-E138K plus IN-G140S/Q148H mutant viruses had significantly greater fold increases in 50% inhibitory concentration (IC(50)) of EFV than viruses carrying a single NNRTI mutation. Likewise, the RT-E138K plus IN-G140S/Q148H mutant virus had significantly greater fold increases in RAL IC(50) than that of the IN-G140S/Q148H mutant virus. These results suggest that interactions between RT and IN mutations are important for NNRTI and INSTI resistance and viral fitness. IMPORTANCE Nonnucleoside reverse transcriptase inhibitors and integrase inhibitors are used to treat infection with HIV-1. Mutations that confer resistance to these drugs reduce the ability of HIV-1 to reproduce (that is, they decrease viral fitness). It is known that reverse transcriptase and integrase interact and that some mutations can disrupt their interaction, which is necessary for proper functioning of these two enzymes. To determine whether resistance mutations in these enzymes interact, we investigated their effects on drug sensitivity and viral fitness. Although individual drug resistance mutations usually reduced viral fitness, certain combinations of mutations increased fitness. When present in certain combinations, some integrase inhibitor resistance mutations increased resistance to nonnucleoside reverse transcriptase inhibitors and vice versa. Because these drugs are sometimes used together in the treatment of HIV-1 infection, these interactions could make viruses more resistant to both drugs, further limiting their clinical benefit.